Assessment of the consumer's ability to repay a consumer loan - Lajošová, Iveta (Technium Social Sciences Journal, 2023)
The academic thesis analyses the obligations that are connected with the topic of assessing the consumer's ability to repay a consumer loan. The author interprets the obligations in assessing the consumer's ability to repay the loan in the sense of the current de lege lata legislation, which is supplemented by the current case law. The chosen topic is set in the context of Directive 2008/48/EC of the European Parliament and of the Council of 23 April 2008 on credit agreements. The author presents arguments indicating the inadequate implementation of individual directives and decisions of the Court of Justice in the courts' decision-making.